Characteristics of young lecturers in universities of the economic block - Trần Thị Hoài Thu, (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
At economic universities, young lecturers form the majority. The young lecturers, less than 35 years old, new to the lecturing position and at their age of high spirit and responsibility for their profession, will be the next generation of work force of the universities. For they will be the key staffs performing the school activities in the next 5 or 10 years and providing training to the human resources for the national economy. The young lecturers would be the forces to promote scientific development and socio-economy.